Analisis Kualitas Hidup Pasien Program Rehabilitasi Rawat Jalan di BNN Kota Cimahi - Hera Herawati (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Drug abuse has an impact on various aspects of life, both physical, psychological and social. Rehabilitation services are provided to drug abusers with the aim of minimizing these impacts and overcoming dependence on drugs, as well as to improve their quality of life. The instrument used to measure the patient's quality of life was officially issued by WHO and has proven its validity and reliability is the WHOQOL- BREF. The purpose of this study was to describe the quality of life of drug abusers undergoing rehabilitation at the BNN Pratama Clinic in Cimahi City in 2021. This study used a qualitative method with an analytical descriptive approach. The sample in this study were 42 patients who were the total population. The results showed that the value of sig. (2-tailed) on the four dimensions, namely the dimensions of physical health, psychological, social relations and environmental dimensions is 0.000. This shows that the indicator value is <0.05, which means that there is a significant improvement in the quality of life of the patient after receiving outpatient rehabilitation services. The percentage increase is based on scoring on the four dimensions, namely the physical health dimension of 78.57%, the psychological aspect of 85.71%, the social relationship dimension of 73.81% and the environmental dimension of 80, 95%.